2012
DOI: 10.1111/jcpp.12025
|View full text |Cite
|
Sign up to set email alerts
|

Annual Research Review: What is resilience within the social ecology of human development?

Abstract: As this review shows, using this multisystemic social-ecological theory of resilience can inform a deeper understanding of the processes that contribute to positive development under stress. It can also offer practitioners and policy makers a broader perspective on principles for the design and implementation of effective interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
499
1
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 644 publications
(542 citation statements)
references
References 139 publications
(147 reference statements)
25
499
1
17
Order By: Relevance
“…Resilience theory and research also is finally beginning to address a longstanding gap in the empirical literature on global cultural processes and contexts (Masten 2014a;Panter-Brick and Leckman 2013;Ungar 2012;Ungar et al 2013). PYD inherently takes context, including cultural aspects of context, into account.…”
Section: Resultsmentioning
confidence: 99%
“…Resilience theory and research also is finally beginning to address a longstanding gap in the empirical literature on global cultural processes and contexts (Masten 2014a;Panter-Brick and Leckman 2013;Ungar 2012;Ungar et al 2013). PYD inherently takes context, including cultural aspects of context, into account.…”
Section: Resultsmentioning
confidence: 99%
“…Interventions developed to suit this population would benefit from attuning to this attitude to mental health and design interventions adapted to this context. Cultural adaptation and keeping contextual factors at the heart of an intervention align with much of resilience research (Masten, 2014; Ungar et al, 2013), including helping children to build resilience in conflict and complex emergency settings (Jordans et al, 2016; Tol, Song, & Jordans, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to prepare children for such events as well as increase their resilience. Any intervention that aims to foster resilience needs to have a multisystemic approach (Masten, 2014) in order to be effective, accounting for the complexity of children’s environment, their experiences and other factors across various systems: biological, micro, meso, exo, macro and chrono (Ungar, Ghazinour, & Richter, 2013). A systematic review found that interventions that were culturally and contextually adapted resulted in creating a more positive impact on the recipients and their communities (Jordans, Pigott, & Tol, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Rather, it is closely intertwined with both society at large and its social structure, institutions, values and norms (Mayer 2004) and the more proximal life circumstances providing opportunities, resources, and support (e.g., Brown and Prinstein 2011b; Lerner and Steinberg 2009b). In their review article, Ungar et al (2013) advance a similar argument for the study of risk, protection and resiliency in social context, also noting that contextual influences on adolescent development have been mostly confined to these more proximal social contexts. There is a rich psychological literature devoted to research on the significance of the family (i.e., family relationships, parenting style, and family support), school (i.e., class climate, teacher support, social relations to class mates), and peers (i.e., peer/friendship relations, peer support) for adolescent development (e.g., Lerner and Steinberg 2009b).…”
Section: Introductionmentioning
confidence: 96%